2015
DOI: 10.1016/j.molmed.2015.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Cancer nanomedicine: from targeted delivery to combination therapy

Abstract: The advent of nanomedicine marks an unparalleled opportunity to advance the treatment of a variety of diseases, including cancer. The unique properties of nanoparticles, such as large surface-to volume ratio, small size, the ability to encapsulate a variety of drugs, and tunable surface chemistry, gives them many advantages over their bulk counterparts. This includes multivalent surface modification with targeting ligands, efficient navigation of the complex in vivo environment, increased intracellular traffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
411
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 606 publications
(417 citation statements)
references
References 78 publications
(105 reference statements)
0
411
0
6
Order By: Relevance
“…In addition, numerous nanotechnology-based platforms that have the potential to result in more effective and safe therapies have been developed or are currently in development [90,91]. Various carrier functionalizations aimed at improving cellular/tissue targeting and overcoming biological barriers have already been exhaustively reviewed [92][93][94][95][96][97][98], and will not be further discussed in this article. Herein, we discuss whether and how the PC affects the interaction between a NP (functional-future science group Review Corbo, Molinaro, Parodi, Toledano Furman, Salvatore & Tasciotti ized or not) and its cellular target, as well as the general mechanisms of that interaction.…”
Section: Impact Of the Pc On The Targeting Capability Of Npsmentioning
confidence: 99%
“…In addition, numerous nanotechnology-based platforms that have the potential to result in more effective and safe therapies have been developed or are currently in development [90,91]. Various carrier functionalizations aimed at improving cellular/tissue targeting and overcoming biological barriers have already been exhaustively reviewed [92][93][94][95][96][97][98], and will not be further discussed in this article. Herein, we discuss whether and how the PC affects the interaction between a NP (functional-future science group Review Corbo, Molinaro, Parodi, Toledano Furman, Salvatore & Tasciotti ized or not) and its cellular target, as well as the general mechanisms of that interaction.…”
Section: Impact Of the Pc On The Targeting Capability Of Npsmentioning
confidence: 99%
“…Cancer remains a major healthcare problem in the world despite strong research efforts toward tackling the disease [1][2]. The nanomedicine seems to be the promising approach in designing the cancer therapies, mainly because nanosystems for the drug delivery have likelihood to increase the circulation halflife of the drug(s), improve pharmacokinetics, and reduce side effects [3].…”
Section: Introductionmentioning
confidence: 99%
“…[468] Such nanoparticles appear to have the highest internalization and modest exocytosis rates, [469] while nanoparticles with hydrodynamic sizes larger than 60 nm are poorly taken up by tumor cells. [470] In a recent study, Salva et al have also reported that manganese oxide nanoparticle with an average [461] Copyright 2015, Elsevier. b) Adapted with permission.…”
Section: Passive Targetingmentioning
confidence: 98%